Sistem Pendukung Keputusan Pemilihan Kepala Divisi Baru FBS Hotel Menara Lexus Menggunakan Metode ROC dan MABAC - Sarmalia Situmorang (STMIK Budi Darma, 2022)
Hotel Menara Lexus is a business engaged in the field of lodging through the provision of room service and food and beverage providers. FBS or Food Bervarage Service is part of the hotel sector unit that manages and is responsible for food service needs and other needs and is managed professionally and commercially. In selecting the head of the new FBS division at the Menara Lexus Hotel, it is sometimes difficult to select and identify the right candidate through direct data and conducting an evaluation system that is still subjective. Sometimes errors in the selection process result in less than optimal work results, which can be a barrier to employee performance. In solving existing problems, the ROC and MABAC methods are used. The ROC method is used as a way to solve the problem of searching for criteria weight values, while the MABAC method is used in selecting candidates to be promoted as new division heads. The results in the research conducted by analyzing the two methods used were that the application of the ROC and MABAC methods produced a candidate information that had the highest score, namely Nehemia with a value of 0.41 in the selection process.